Local Characterization of Field Emission Properties of Graphene Flowers. (15th November 2022) - Giubileo, Filippo; Capista, Daniele; Faella, Enver; Pelella, Aniello; Kim, Woo Young; Benassi, Paola; Passacantando, Maurizio; Di Bartolomeo, Antonio
Abstract: An experimental study about field emission properties of commercially available graphene flowers cloth is reported. Material characterization by means of X‐ray diffraction, Raman spectroscopy, and X‐ray photoemission spectroscopy confirms the formation of high quality vertical few‐layers graphene nanosheets. A tip‐anode setup is exploited in which nanomanipulated tungsten tip is used as the anode at controlled distance from the emitter in order to reduce the effective emitting area below 1 µm 2, giving access to local characterization. A turn‐on field as low as 0.07 V nm −1 and field enhancement factor up to 32 for very small cathode–anode separation distances is demonstrated, in the range 400–700 nm. It is also shown that the turn‐on field increases for increasing distances, while the field enhancement factor decreases. Finally, time stability of the field emission current is reported, evidencing a reduction of the fluctuations for lower current levels. Abstract : A nanomanipulated tip‐shaped anode is used inside a scanning electron microscope to characterize the local field emission properties of graphene flowers cloth demonstrating good time stability and a turn‐on field as low as 0.07 V nm −1 when the anode is 400 nm away from the emitting surface, with an increasing dependence for increasing distance up to 700 nm.